2019
DOI: 10.7589/2017-10-257
|View full text |Cite
|
Sign up to set email alerts
|

Regional and Age-Related Variations in Haptoglobin Concentrations in Steller Sea Lions (Eumetopias Jubatus) From Alaska, Usa

Abstract: Varying concentrations of the highly conserved acute phase response protein, haptoglobin, can indicate changes to the health and disease status of mammals, including the Steller sea lion ( Eumetopias jubatus; SSL). To better understand factors relating to acute phase response in SSLs, circulating haptoglobin concentrations (Hp) were quantified in plasma collected from 1,272 individuals sampled near rookeries and haulouts off the coast of Alaska. We compared Hp in SSLs between sexes and among different age clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…It is possible that reproductive differences would emerge if turtles were sampled at more time points during the active season. Seasonal differences in HBP concentrations have been identified in Pyrenean chamois (Rubricapra pyrenaica pyrenaica) and site differences have been detected in Steller sea lions, indicating the potential need for season and population-specific reference intervals [10,91,94]. All HBP measurements in the present study came from a single box turtle population that was serially sampled over the course of three years, and the potential for seasonal and population-level variability in this analyte is unknown.…”
Section: Plos Onementioning
confidence: 90%
“…It is possible that reproductive differences would emerge if turtles were sampled at more time points during the active season. Seasonal differences in HBP concentrations have been identified in Pyrenean chamois (Rubricapra pyrenaica pyrenaica) and site differences have been detected in Steller sea lions, indicating the potential need for season and population-specific reference intervals [10,91,94]. All HBP measurements in the present study came from a single box turtle population that was serially sampled over the course of three years, and the potential for seasonal and population-level variability in this analyte is unknown.…”
Section: Plos Onementioning
confidence: 90%
“…Full assay validation has not been performed for any APR assay in nondomesticated mammal species, and some studies provide no information about assay validation 16–18,20–29 . When validation has been performed, this usually only includes imprecision and linearity experiments, 22,30–38 sometimes with additional recovery or limit of detection studies 13,39–46 (Tables 1‐4).…”
Section: Methodsmentioning
confidence: 99%
“…Haptoglobin has been proposed as a bioindicator, but a lack of attention to assay validation and the use of varying methods confounds the interpretation of results. For example, two studies measured haptoglobin in the same population of Steller sea lions and harbor seals in the Gulf of Alaska 25,29 . Populations in the western portion of this ecosystem were declining and were considered endangered, while populations in the eastern portion were stable.…”
Section: Applicationsmentioning
confidence: 99%
“…Many factors have been implicated in the lack of recovery (Atkinson et al, 2008); studies reporting relatively high and spatially dependent concentrations of total mercury ([THg]) in wDPS Steller sea lion tissues (Correa et al, 2014; Rea et al, 2020) raise concern about the potential for Hg‐associated biological effects. Similar to other marine mammals (Dietz et al, 2019), recent studies of Steller sea lions have reported Hg‐associated effects on immunological parameters (Kennedy et al, 2019; Levin et al, 2020), although direct cause and effect in wild populations can be difficult to assess. Archived tissues can be a valuable resource for assessing Hg and selenium (Se) in wild populations, but interpretation requires an understanding of organotropism across age cohorts.…”
Section: Introductionmentioning
confidence: 95%